Pengelolaan Lembaga Sertifikasi Profesi (LSP-P1) dalam Menyiapkan Lulusan Perguruan Tinggi di Dunia Kerja - Aji Prasetyo; Brahmana Rangga Prastyana; Very Ferdiansyah Eka Putra; Dendy Pramudya Adytya (Southeast Asian Journal of Islamic Education Management, 2023)
The Management System for Professional Certification Institution in Higher Education prepares students for work. Professional Certification Institution also promotes competency certification as a means of student competency recognition. Studying the competency certification mechanism at Professional Certification Institutions-P1 in Higher Education is necessary. This study examined the advantages and disadvantages of Professional Certification Institution-P1 management in higher education. This study uses a qualitative approach with a case study design. The subjects of this study were the Professional Certification Institution-P1 Head, Certification Manager, and Quality Manager. Research data were collected through observations, interviews, and documentation and analyzed using triangulation to provide valid data. An interactive analysis model analyzed triangulated data (Interactive model analysis). While, Interviews, observations, and documentation provided a general description of the Professional Certification Institution's competence certification mechanism, which follows professional certification body number 04/BNSP.305/ X/2013 concerning the test guidelines. In addition, higher education institutions are developing Professional Certification Institution management by increasing the number and quality of assessors for competency test activities and certification schemes. The National Education Education Standards Agency (BNSP) guidelines and university leaders' support have guided management's advantages and disadvantages. The Professional Certification Institution-P1 needs to conduct more socialization on students for competency test participation. Thus, it can be concluded that this study shows that East Java universities generally follow National Education Standards Agency guidelines for managing Professional Certification Institutions.